Impact of Platelet Count on Non-ST Elevation Myocardial Infarction: In-Hospital Outcome (Medicine Today, 2022)
Introduction: Incidence of ACS is increasing in developing countries like Bangladesh. Many factors can influence in hospital outcome of NSTEMI Patient. Platelet count is one of them. The aim of present study was by measuring platelet count to detect the severity of NSTEMI patients and their in hospital outcome.Objective: The aim of present study was to observe the impact of platelet counts on in hospital outcome of NSTEMI.Materials and Methods: The study was conducted in Shahid Sheikh Abu Naser Specialized Hospital, Khulna from January 2021 to November-2021. NSTEMI Patient Presented within 24 hours of chest pain was included in this study. Data were collected by direct interview from Patient and venous blood was drawn for platelet count. Continuous data were expressed as mean ±SD. Categorical data were analyzed with x2 test. Student’s ‘t’ test was used for analysis of Continuous variables. Comparision between groups was done by unpaired t-test. Multiple logistic regression analysis was done to determine the association between lower platelet counts and adverse hospital events in NSTEMI patients. P-values